EPCT-07. Updated report on the pilot study of using MRI-guided laser heat ablation to induce disruption of the peritumoral blood brain barrier to enhance deliver and efficacy of treatment of pediatric brain tumors. (3rd June 2022) - Shatara, Margaret; Gauvain, Karen; Cantor, Evan; Meyer, Ashley; Ogle, Andrea; McHugh, Michele; Beck, Mary; Green, Tammy; King, Allison; Cluster, Andrew; Brossier, Nicole; Shimony, Joshua S; et al.
Abstract: BACKGROUND: MRI-guided laser interstitial thermal therapy (LITT) is a minimally invasive, cytoreductive surgery useful for managing unresectable brain tumors. LITT disrupts the blood brain barrier (BBB) and facilitates chemotherapy delivery. We report the toxicity and outcome for pediatric brain tumors treated on a pilot trial of LITT and chemotherapy. The primary objectives were to quantify peritumoral BBB disruption following LITT and evaluate toxicity and efficacy. METHODS: The trial had two arms, A: patients with newly diagnosed gliomas underwent LITT followed by standard of care management, and B: patients with relapsed malignant brain tumors received 6 weeks of weekly doxorubicin post-LITT followed by maintenance etoposide. RESULTS: Between 2015 – 2018, six patients were enrolled: five on arm A (four with low-grade gliomas, one with high-grade glioma), one on Arm B with progressive anaplastic astrocytoma. All patients tolerated the procedure well; four experienced a transient hemiparesis post-LITT. The Arm B patient progressed and died of disease 2 months and 22 months post-LITT, respectively. The HGG patient received standard therapy and remains without disease progression 44 months post-LITT. One patient with LGG required additional treatment for disease progression 14 months post-LITT. Two patients with LGGs did not require additional therapy, now 51 and 41 months post-LITT. One patient was alive 24 weeks post-LITT and subsequently lost to follow-up. Peritumoral BBB disruption was analyzed in two ways: serum abundance of brain-derived proteins and MRI Dynamic contrast enhancement (DCE). Neuron-specific enolase were measurable in the serum of all patients, using ELISA up to 84 days post-LITT. DCE 2 weeks post-LITT demonstrated increased enhancement and FLAIR signal, consistent with BBB disruption and vasogenic edema. This effect was evident up to 4 months post-procedure. CONCLUSION: LITT is safe in children with brain tumors and can be combined with chemotherapy. DCE and serum brain-derived proteins can measure BBB disruption.